Disparities in Cholangiocarcinoma Research and Trials: Challenges and Opportunities in the United States - Oyepeju F. Abioye; Rebekah Kaufman; Tim F. Greten; Cecilia Monge (JCO Global Oncology)
Cancer disparities are well-established across measures of cancer incidence and mortality. Cholangiocarcinoma, a common hepatic malignancy, is no exception to these inequities. Globally and within the United States, Asian, Hispanic, and Indigenous peoples of the Americas, Alaskan Natives, and Pacific Islander populations experience higher incidence rates of cholangiocarcinoma. These same groups and non-Hispanic Black individuals simultaneously experience lower disease-specific survival, highlighting the role of social factors in cholangiocarcinoma outcome inequities. Higher age-standardized death rates from cholangiocarcinoma are associated with a lower social determinant index (SDI) in Andean Latin America, Southern Latin America, and Central sub-Saharan Africa. SDI, which evaluates education, fertility, and income, can be used to model the social determinants of health (SDOH). The SDOH also affect cholangiocarcinoma survival in the United States as factors such as migratory status, insurance status, and geographic location can cause treatment delays and worsened outcomes. Despite these inequities, limited research exists on the topic of disparities in cholangiocarcinoma when compared with other malignancies, and clinical trial under-representation remains a significant concern. Representing diverse populations in cholangiocarcinoma clinical trials is exceedingly important as populations with the highest incidence are simultaneously under-represented in clinical trials. Diversity in clinical trial enrollment and research regarding cholangiocarcinoma is needed to create robust databases and biobanks that can be used to develop targeted treatments and guidelines. In addition, risk factors, including parasitic infections, infectious diseases, and environmental exposures, are associated with cholangiocarcinoma but vary by global region, highlighting the need to study unique risk factors for cholangiocarcinoma across diverse populations. Without research that represents the populations that suffer most from this cancer, incidence and mortality inequities will continue to have a disproportionate burden.